Antibiotic resistance microbes in tropical mangrove sediments, East Coast Peninsular, Malaysia - Khan Chowdhury, Ahmed Jalal; U T, Nur Fatin; Mohd Ashaari, Mardiana; John, Akbar; Yunus, Kamaruzzaman; Saad, Shahbudin; Omar, Muhammad Nor (Academic Journals, 2010)
The study has been conducted at Tanjung Lumpur, mangrove swamp on January 2009 to isolate and identify the bacterial community in mangrove soil and their resistance against antibiotics. Identified bacteria were Aeromonas hydrophila group 1 and 2, Escherichia coli 1, Chryseomonas luteola, Chromobacterium violaceum, Pseudomonas aeruginosa, Serratia rubudaea, Klebsiella pnuemoniae and Enterobacter cloacae. The identified bacteria were introduced to fourteen different antibiotics to determine the bacterial susceptibility. All the isolates showed 100% resistant towards β-lactam antibiotics (ampicillin, amoxicillin and penicillin), vancomycin, sulphafurazole, gentamicin, erythromycin, tetracycline, novobiocin, clindamycin and bacitracin indicates the presence of bacterial amidases and β-lactamases in the bacteria which inhibit the action of β- lactam antibiotics. Bacteria isolated from mangrove soil showed 66.7 and 77.8% resistance against chloramphenicol and streptomycin, respectively, suggesting that the lipid composition might play a key role in preventing the entrance or binding of antibiotic to the cell. All the isolates were susceptible to ciprofloxacin since it inhibits the enzyme topoisomerase II that cause the negative super coil in DNA and thus permits transcription or replication. All bacterial isolates showed Multi Antibiotic Resistance (MAR) index higher than 0.2 and proved high-risk sources of contamination of the environment. This study proved the presence of antibiotic resistant bacterial strains in mangrove soil that could be used for further studies.